Predictors of match performance in the South African Rugby Union Women's Premier Division - Sewry, N.; MacMillan, C.; Maree, W.; Readhead, C.; Cantwell, L.; Jordaan, E.; Swanevelder, S. (International Journal of Sports Science & Coaching, 2024)
Purpose Performance indicators in women's rugby union are under-researched. The aim of this study was to describe the match activities and determine the predictors for winning/losing and points difference in the South African Rugby Union (SARU) Women's Premier Division competition.